P151 Real time reporting pilot in end of life care. (1st October 2013) - Bake, Jane; Cooper, Marie
Abstract : Background: It is acknowledged that to date, capturing meaningful and timely feedback from patients within the last year of life, and their families, remains a challenge. Project aim and objectives: The objectives of the project were to ascertain the acceptability and usefulness of a real time survey and reporting system to capture the experience of patients, families and carers receiving end of life care. Organisations within Lincolnshire were invited to join the pilot and four different care settings, where end of life care is commonly provided were engaged; care home, persons own home, hospice and hospital. Approach: Survey questions were tailored to each care setting with volunteers and staff inviting participants to use a hand held 'ipad' device to feedback their experience of care; alternative options, such as web link and paper survey, were also offered. Outcomes and application: The pilot was successfully implemented across all four different care settings. The use of the devices and the length of the survey were acceptable to individual receiving care and their family member. The trial of a reworded 'family & friends 'question with those at the end of life proved acceptable to the majority of users The role of the volunteer was instrumental in engaging participants. Volunteers expressed satisfaction and reported back on the added value of one to one engagement with survey participants. Anecdotal feedback from the volunteers and staff suggested that patients and carers were happy to participate and expressed enjoyment in taking part. "Patients appreciate the opportunity to speak to someone and to have their voice heard as well as trying new technology" Provides timely, concise and meaningful information to service providers Provides opportunities for organisations to benchmark end of life care county-wide Next phase will seek to inform on further learning for a national roll out